Widowhood and associated risks in under-resourced communities: A Social Work Perspective - Dube, Misheck (Technium Social Sciences Journal, 2021)
The perpetual growth in the population of widows globally signals the need for systematic research and interrogation of the phenomenon of widowhood. Under-resourced communities have been side-lined from imperative investigations and systematic documentation to inform practice. This article discusses the risks associated with widowhood in under-resourced communities of Binga District in Zimbabwe. Following a qualitative research approach and a phenomenological research design, purposive sampling was employed to engage ten widows in one-on-one in-depth interviews. Data were analysed thematically and backed up by existing literature to provide thick descriptions. The findings of the study indicated that widows were exposed to an arsenal of health, psychological, social and economic risks. Many of the risks associated with widowhood are exacerbated by lack of supportive environments and provision of conducive environment to trigger proper adaptation mechanism especially among the young widows in under-resourced communities. The conclusions reached were that widowhood risk factors continue to increase among widows in under-resourced communities impacting negatively on optimal living and adaptation with the widows’ circumstances.